Imidazolium‐Functionalized Carbon Nanohorns for the Conversion of Carbon Dioxide: Unprecedented Increase of Catalytic Activity after Recycling. Issue 6 (28th December 2016) - Calabrese, Carla; Liotta, Leonarda F.; Carbonell, Esther; Giacalone, Francesco; Gruttadauria, Michelangelo; Aprile, Carmela
Abstract: Six new hybrid materials composed of carbon nanohorns (CNHs) and highly cross‐linked imidazolium salts were easily synthesized using a one‐step procedure based on the radical oligomerization of bis‐vinylimidazolium salts (bVImiX) in the presence of pristine CNHs. The hybrid materials were characterized and employed as the sole catalysts for the conversion of carbon dioxide into cyclic carbonate by reaction with epoxides. The solids displayed excellent turnover number and productivity. Moreover, four catalysts were investigated in recycling experiments. Two catalysts containing an octyl linker between the imidazolium units and a bromide or an iodide anion showed no loss in activity after three cycles. The other two catalysts containing a p ‐xylyl linker and a bromide anion and different CNHs/bVImiX ratios showed an unprecedented increase of activity after recycling. Abstract : It keeps getting better ! Carbon nanohorns functionalized with imidazolium salts were synthesized using a straightforward one‐pot procedure and used as catalysts for the conversion of carbon dioxide. The solids displayed excellent turnover number and productivity. Moreover, the catalysts having a p ‐xylyl linker and bromide anion showed an unprecedented increase of activity.